Analyzing the Impact of X-Pert System and Training on Employee Performance at Hotel X Bandung - Indriana Kurnia Cahyati; Mery Adelia; Sherry Novalia Fujiasti (Jurnal Manajemen dan Profesional, 2026)
This research aims to analyze the impact of the X-Pert Hotel System and employee training on performance at Hotel X using a quantitative explanatory survey with purposive sampling. Data were gathered through questionnaires and subsequently  processed using the Partial Least Squares (PLS). The findings indicate that employee training has a positive and significant effect on performance by improving efficiency and effectiveness in system usage, while its integration with the X-Pert Hotel System enhances employee productivity and supports overall hotel operations.